Perhitungan Poros Roda Depan Motor Supra X 125 Helm In - Iwan Nugraha Gusniar; Muhamad Fadhlan Suhelmi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The shaft is one component of a motorcycle that is no less important than other components. These components function to support the load of the vehicle itself as well as external loads such as humans or cargo on a motorcycle. This study aims to determine the working stress and also the safety factor on the shaft. The component that will be discussed is the front axle of the Supra X 125 Helm In motorcycle. The method used is an experimental method with qualitative and quantitative analysis. The results of the analysis show that if a load of 70 kg is given, then the value of the working stress is 230.45 N/mm2, while the safety factor is 1.488